Data Disparities and Overlaps in Smart Indonesia Card (KIP) Recipients Studying at State Islamic Religious Universities (PTKIN) - Shofiyah M (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This Policy Paper analyzes the problem of overlapping recipients of the KIP Kuliah Program at State Islamic Religious Colleges (PTKIN), which stems from a lack of coordination between internal units. This program should be a vital instrument for ensuring educational access for students from underprivileged families, but its implementation in the field is hampered by administrative inefficiencies. There are cases where a student receives KIP Kuliah simultaneously with another scholarship from a different unit within the same campus, indicating a systematic failure in data integration. This paper uses a qualitative method with a descriptive analysis approach and a literature review. Data were collected through a literature review related to scholarship governance, annual reports of student programs, and applicable internal regulations. The analysis process was conducted descriptively to identify patterns and relationships between organizational structures, communication flows, and their impact on the accuracy of aid distribution. Through this review, it was found that work silos and the absence of a centralized data platform were the main causes of aid duplication. This document aims to formulate practical recommendations for improving governance, which include the formation of an integrated coordination team and the implementation of an integrated management information system, to ensure that KIP Kuliah assistance is truly on target and provides maximum impact on student welfare.